Anti-inflammatory and antioxidant properties of oleuropein in human keratinocytes characterized by bottom-up proteomics - Li, Huifang; Deng, Ni; Yang, Jiayi; Zhao, Yang; Jin, Xiaoxuan; Cai, Ang; Seeram, Navindra P.; Ma, Hang; Li, Dongli; Yang, Huilan; Liu, Chang (Frontiers in Pharmacology, 2025)
Oleuropein is a phenolic compound commonly found in cosmetic ingredients including olive leaves and jasmine flowers with various skin-beneficial effects. Here, we evaluated oleuropein’s anti-inflammatory and antioxidant activities in human skin cells. In a cell-based inflammasome model with human monocytes (THP-1 cells), oleuropein (12–200 µM) reduced proinflammatory cytokine interleukin (IL)-6 by 38.8%–45.5%, respectively. Oleuropein (50 and 100 µM) also alleviated oxidative stress in keratinocytes (HaCaT cells) by reducing H2O2-induced cell death by 6.4% and 9.2%, respectively. Additionally, biological evaluations revealed that oleuropein’s antioxidant effects were attributed to its mitigation of reactive oxygen species in HaCaT cells. Furthermore, a multiplexed gene assay identified IL-1β and thioredoxin-interacting proteins as potential molecular targets involved in oleuropein’s protective effects in HaCaT cells. This was supported by findings from several cellular assays showing that oleuropein reduced the level of IL-1β and inhibited the activity of caspase-1/IL-1 converting enzyme, as well as ameliorated pyroptosis in HaCaT cells. Moreover, a bottom-up proteomics study was conducted to explore potential molecular targets and signaling pathways involved in oleuropein’s antioxidant activities. Taken together, findings from this study expand the understanding of oleuropein’s skin protective effects against oxidative and inflammatory stresses, which support that oleuropein is a promising natural cosmeceutical for skincare applications.